Moluscos marinhos de ampla distribuição latitudinal - Rios, Eliézer de C.; Loyola e Silva, Jayme de; Matthews, Henry R. (Acta Biológica Paranaense, 1975)
Moluscos marinhos de ampla distribuição latitudinal